Cabrero, Enrique, Acción pública y desarrollo local, México, FCE, 2005 - Ugalde, Vicente (Estudios Demográficos y Urbanos, 2006)
Cabrero, Enrique. (2005). Acción pública y desarrollo local, México, FCE.